EA and Climate Change Mitigation - Koehl, Albert (Journal of Environmental Law and Practice, 2010)
The Canadian Environmental Assessment Act (CEAA), as well as comparable laws such as the Ontario Environmental Assessment Act, is precisely the type of law one would expect to play a role in mitigating greenhouse gas (GHG) emissions from new projects. Unfortunately, in practice, CEAA is proving to be a failure in reducing or even stabilizing ever-increasing Canadian GHG emissions most notably from the oil and gas sector, particularly the tar sands. This article explores the reasons why CEAA has thus far disappointed advocates hoping to see the mitigation of GHG emissions from new projects. The author suggests that headway in reducing GHG emissions may nonetheless be made under CEAA by convincing courts that significance can only be defined in a manner consistent with the dictates of climate science. In particular, a focus on cumulative effects may help define significance in a more climate-friendly manner. The article also explores law reform options that would make CEAA a more effective tool in addressing climate change.